Optoelectric Properties of GaInP p-i-n Solar Cells with Different i-Layer Thicknesses - Tsung-Shine Ko; Der-Yuh Lin; You-Chi He; Chen-Chia Kao; Bo-Yuan Hu; Ray-Hua Horng; Fan-Lei Wu; Chih-Hung Wu; Yu-Li Tsai (International Journal of Photoenergy)
The optoelectric properties of GaInP p-i-n solar cells with different intrinsic layer (i-layer) thicknesses from 0.25 to 1 μm were studied. Both emission intensity and full width at half maximum features of the photoluminescence spectrum indicate that the optimum i-layer thickness would be between 0.5 and 0.75 μm. The integrated current results of photocurrent experiment also point out that the samples with 0.5 to 0.75 μm i-layer thicknesses have optimum value around 156 nA. Electroreflectance measurements reveal that the built-in electric field strength of the sample gradually deviates from the theoretical value larger when i-layer thickness of the sample is thicker than 0.75 μm. I-V measurements also confirm crystal quality for whole samples by obtaining the information about short currents of photovoltaic performances. A series of experiments reflect that thicker i-layer structure would induce more defects generation lowering crystal quality.